2014
DOI: 10.1016/j.juro.2014.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Muscle Derived Cells for Treatment of Stress Urinary Incontinence in Women

Abstract: Autologous muscle derived cells for urinary sphincter repair at doses of 10, 50, 100 and 200×10(6) cells appears safe. Efficacy data suggest a potential dose response with a greater percentage of patients responsive to higher doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 11 publications
0
90
0
Order By: Relevance
“…They found that higher-dose groups (100 × 10 6 and 200 × 10 6 MDCs) were associated with greater response in terms of reduction in SUI frequency and pad weight. 26 Similarly, other clinical trials using myoblasts or MDSCs in treatment of female SUI were published by Blaganje et al, 27 Carr et al, 28 and Stangel-Wojcikiewicz. 29 All of them confirmed a high safety profile and encouraging short-term success rates in stem-cell-based therapy for SUI treatment.…”
Section: Future Sui Treatmentsmentioning
confidence: 89%
See 1 more Smart Citation
“…They found that higher-dose groups (100 × 10 6 and 200 × 10 6 MDCs) were associated with greater response in terms of reduction in SUI frequency and pad weight. 26 Similarly, other clinical trials using myoblasts or MDSCs in treatment of female SUI were published by Blaganje et al, 27 Carr et al, 28 and Stangel-Wojcikiewicz. 29 All of them confirmed a high safety profile and encouraging short-term success rates in stem-cell-based therapy for SUI treatment.…”
Section: Future Sui Treatmentsmentioning
confidence: 89%
“…The data showed that injection of autologous muscle-derived cells did not lead to any adverse outcomes after 12 months of followup. 26 In the near future, tissue engineering strategies may increasingly be applied, as various bioengineered degradable scaffolds have been proposed and studied in animal models.…”
Section: Future Sui Treatmentsmentioning
confidence: 99%
“…A pooled mean was calculated from all three resulting in an estimated base case cure rate of 68%. Although there are other studies in the literature showing similar efficiency for IVM, they were not included here due to lack of definition the 'cured' patient population [34,35]. All patients not included in the group of 'cured' were added to the group 'not cured', despite having shown improvements.…”
Section: Probabilitiesmentioning
confidence: 99%
“…22 Trials have shown positive effects without serious adverse effects. In those studies, however, cells are administered a long time after the causal injury, in symptomatic patients.…”
Section: Clinical Scenario and Identification Of Potential Beneficiariesmentioning
confidence: 99%